2022
DOI: 10.3389/fnagi.2022.930315
|View full text |Cite
|
Sign up to set email alerts
|

Sleepiness in Cognitively Unimpaired Older Adults Is Associated With CSF Biomarkers of Inflammation and Axonal Integrity

Abstract: IntroductionSleepiness has been associated with cognitive decline and dementia in the elderly. Older adults with excessive daytime sleepiness appear to be more vulnerable to longitudinal amyloid PET accumulation before the onset of the dementia. However, it remains unclear whether sleepiness is similarly associated with other biomarkers of Alzheimer’s disease (AD), axonal integrity, and inflammation, which may also contribute to neurodegeneration and cognitive decline.MethodsIn this cross-sectional analysis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 127 publications
2
6
0
Order By: Relevance
“…The impact of SCI on future dementia is partially mediated by NfL (proportion of total effect that is mediated: 0.229). The relationships between SCI and NfL, as well as NfL and dementia, have been confirmed in several previous studies 10,45,46 . Interestingly, in the Sleep+ group, we observed that SCI fully mediated the relationship between GDS and Aβ42/40 (proportion of total effect that is mediated: 0.715).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The impact of SCI on future dementia is partially mediated by NfL (proportion of total effect that is mediated: 0.229). The relationships between SCI and NfL, as well as NfL and dementia, have been confirmed in several previous studies 10,45,46 . Interestingly, in the Sleep+ group, we observed that SCI fully mediated the relationship between GDS and Aβ42/40 (proportion of total effect that is mediated: 0.715).…”
Section: Discussionsupporting
confidence: 89%
“…The relationships between SCI and NfL, as well as NfL and dementia, have been confirmed in several previous studies. 10,45,46 Interestingly, in the Sleep+ group, we observed that SCI fully mediated the relationship between GDS and Aβ42/40 (proportion of total effect that is mediated: 0.715). This finding is not surprising as previous research has reported a strong negative correlation between GDS and Aβ42/40.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We have shown higher rates of amyloid PET accumulation in individuals without dementia with excessive daytime sleepiness 13 and higher tau PET levels in cognitively unimpaired (CU) individuals with higher risk for obstructive sleep apnea (OSA), 14 consistent with other evidence supporting a bidirectional relationship between sleep disorders and AD pathology. 15 However, we have also found an increase in CSF neurofilament light chain in CU individuals with daytime sleepiness, suggesting that sleep disturbance may be associated with underlying WM injury, 16 concerning for coexistent vascular pathology. This is particularly relevant in patients with OSA, which has been extensively associated with CVD.…”
mentioning
confidence: 63%